If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -5 = 3(x + -6) Reorder the terms: -5 + y = 3(x + -6) Reorder the terms: -5 + y = 3(-6 + x) -5 + y = (-6 * 3 + x * 3) -5 + y = (-18 + 3x) Solving -5 + y = -18 + 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + y = -18 + 5 + 3x Combine like terms: -5 + 5 = 0 0 + y = -18 + 5 + 3x y = -18 + 5 + 3x Combine like terms: -18 + 5 = -13 y = -13 + 3x Simplifying y = -13 + 3x
| 9x+y=72 | | (11x)-5=180 | | x/3=5+x-5/5 | | x/9=3x/7-20 | | 1+2=? | | 1+2=8 | | 2. 3/2y-d4=5/3(y+4)-2/3 | | x^2-5=-4x^2-3x | | 36x-100-4(x^2)=0 | | x/2-1=x/5+1 | | 9p-6q=20 | | 2x=73-3 | | 5y+2y+12=4y-4-2 | | 16x^2-8x+1=-x^2+5 | | 7+3x=22-10x | | H-17=17 | | 3/2y-4=5/3(y+4)-2/3 | | 3(xX-5)=21 | | 24-n=7 | | 7+3x=2[11-5X] | | A+37=42 | | -3x+9y=57 | | 5x-y=54 | | 18-3x=13+2x | | 2x-8+31=180 | | 17x+9/2-16x=1/8 | | x+15/7=-2/7 | | 9(x+2)-3=3x+6(3+x) | | 4(x+2)-8=2x+2(-2+x) | | 4(x+2)-8=2x+(-2+x) | | 6x+3=-3+14 | | 14-(6x-5)=5(2x-1)-4 |